Clinical application of amino-terminal pro-brain natriuretic peptide concentration in amniotic fluid for the prediction of preterm birth in symptomatic womenAJOG Global Reports at a Glance - Fernando A. Ferrer-Marquez, MD; Rocío P. Astudillo, MD; Jorge A. Carvajal, MD, PhD (Elsevier, 2024)
BACKGROUND: Preterm birth accounts for 60% to 80% of neonatal mortality. Approximately one-third of preterm births are caused by the spontaneous onset of preterm labor. Nevertheless, 70% to 90% of women diagnosed with preterm labor will not deliver within 7 days. Thus, many women will be unnecessarily treated by preterm labor with risk medications. Better tools are needed to categorize women in preterm labor into high or low risk of preterm delivery. OBJECTIVE: This study aimed to evaluate the amino-terminal pro-brain natriuretic peptide concentration in the amniotic fluid as a prognostic test to predict the risk of delivery within 48 hours or 7 days and before 34 0/7 or 37 0/7 weeks of gestation in women in preterm labor. STUDY DESIGN: A total of 102 pregnant women presenting signs and symptoms of spontaneous preterm birth (22 0/7 to 34 0/7 weeks of gestation) were included. Amniotic fluid was obtained by amniocentesis, and amino-terminal pro-brain natriuretic peptide concentration was measured. Below normal concentration was defined as <0.5 multiples of the median of the standard curve according to gestational age. The risk of preterm delivery was estimated according to normal or lower-than-normal amino-terminal pro-brain natriuretic peptide concentrations. The predictive capacity of the test (below normal amino-terminal pro-brain natriuretic peptide concentration) was evaluated to identify spontaneous preterm birth at 48 hours or 7 days from amniocentesis and less than 34 0/7 or 37 0/7 weeks at delivery. RESULTS: For the outcome delivery within 48 hours, lower-than-normal amino-terminal pro-brain natriuretic peptide concentration had 94.6% sensitivity, 73.8% specificity, 96.0% negative predictive value, 3.61 positive likelihood ratio, and 0.07 negative likelihood ratio. For the outcome delivery within 7 days, the test had 93.9% sensitivity, 88.7% specificity, 94.0% negative predictive value, 8.31 positive likelihood ratio, and 0.07 negative likelihood ratio. For the outcomes of spontaneous preterm birth before 34 0/7 and 37 0/7 weeks of gestation, below normal amino-terminal pro-brain natriuretic peptide concentrations had 80.0% sensitivity, 83.0% specificity, 78.0% negative predictive value, 4.70 positive likelihood ratio, and 0.24 negative likelihood ratio and 64.1% sensitivity, 91.7% specificity, 44.0% negative predictive value, 7.70 positive likelihood ratio, and 0.39 negative likelihood ratio, respectively. CONCLUSION: Among patients in spontaneous preterm labor, the detection of lower-than-normal amino-terminal pro-brain natriuretic peptide concentrations (<0.5 multiples of the median) in amniotic fluid has an excellent predictive capacity to identify those patients at low risk of preterm delivery within 48 hours or 7 days.